A Systematic Review of Diagnoses With Rosettes Under Dermoscopy - May Alorainy; Kendall Buchanan; Tyler Nussinow; Judy B. Rabinowitz; Peggy Cyr; Elizabeth V. Seiverling (Mattioli1885, 2024)
Introduction: Rosettes are a cluster of shiny white dots in the shape of a four-leaf clover seen under polarized dermoscopic light. Historically, rosettes were primarily reported in actinic keratoses and squamous cell carcinoma. However, rosettes have also been reported in other conditions. Objectives: The objective of this systematic review to elucidate the breadth of diagnoses exhibiting this unique dermoscopic phenomenon. Methods: A review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Literature searches were performed in MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials and Web of Science, as well as a manual search of the reference lists of screened articles. Results: A total of 73 articles met the inclusion criteria. Out of these, 47 distinct diagnoses with rosette were identified. Among neoplastic conditions, keratinizing neoplasms had the highest number of articles reported (n=19). Discoid lupus was the most commonly reported diagnosis within the inflammatory category (n = 6). Molluscum contagiosum was the predominant diagnosis among infectious entities (n = 3), while acroangiodermatitis was the sole diagnosis reported in the vascular category (n = 1). Conclusion: These findings confirm rosettes are not specific to keratinocytic growths and are observed in a wide range of conditions. Knowledge of the breadth of conditions with rosettes may aid clinicians when developing a differential diagnosis of a growth or an eruption with rosettes under dermoscopy.